Test-retest reliability and sensitivity of senior elite amateur boxers maximal punch force, as quantified by a vertically mounted force plate - Finlay, M. J.; Page, R. M.; Greig, M.; Bridge, C. A. (PLOS ONE, 2023)
An ecologically valid, reliable and sensitive method of quantifying punch force variables would be useful for coaches and practitioners monitoring combat-specific performance. The present study utilised a vertically mounted force plate to quantify the peak punch force and rate of force development (RFD) of amateur boxers. Ten male senior elite amateur boxers performed maximal jab, cross, and hook punches across two separate days. The force plate showed excellent within-day and good-to-excellent between-day reliability for peak punch impact force and RFD (ICC 0.89-0.99). The CV% for all punch force variables were similar on day 1 (3-9%) and day 2 (4-10%). Standard error of measurement (SEM) and smallest worthwhile changes (SWC) revealed the force plate can detect small-to-moderate changes in punch performance. The greatest impact forces and RFD were found in the rear hook (2624 ± 581 N, 296448 ± 101823 N.s-1), followed by the lead hook (2524 ± 532 N, 256813 ± 81735 N.s-1), cross 2425 ± 545 N, 193004 ± 62671 N.s-1) and jab (1645 ± 537 N, 116675 ± 41577 N.s-1). The vertically mounted force plate is a reliable and sensitive test of punch performance, thus may be useful in determining the efficacy of training interventions.